Rancangan Penyelesaian Konflik Pada Organisasi Publik - Sutanto, Djoko (Responsibilitas, 2010)
Abstract Conflict in organization is thing ordinary, but that thing becomes hardly bothers the way organizational wheel when the conflict takes place is continuous without existence of solution. Therefore every organization can must to manage conflict for to fluent the way organization and hereinafter the conflict can be exploited to create productivity. Thereby conflict management done ought to towards at creation solving of conflict. Â  Keyword: Manajenen konflik, Organisasi publik.